Inclusive learning management in realizing adaptive educational services in elementary schools - Linda Tri Utami; Siti Maisaroh (Universitas Sarjanawiyata Tamansiswa, 2025)
This study describes the management of inclusive learning at SD Negeri Brengosan 1, a state elementary school in Sleman, Indonesia. It examines planning, implementation, and evaluation for students with special needs (SEN). Using a qualitative descriptive design, data were collected through observations, interviews with classroom and special education teachers, and documentation, and were analyzed using Miles and Huberman’s interactive model. The findings show that planning involves identifying student needs and collaboratively preparing Individualized Education Programs (IEPs). Implementation highlights curriculum flexibility, cooperative learning, and the use of visual and multisensory media supported by team-teaching. Evaluation is carried out continuously, focusing on individual progress through portfolios and observations rather than standardized tests. Overall, inclusive learning management in this school is collaborative and adaptive, although challenges remain in teacher training and resource availability. These insights offer practical guidance for strengthening inclusive practices in other primary schools.